(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2025)
This study explores the relationship between spatial organization and economic stratification among vendors in Cogon Market, Cagayan de Oro City. Employing qualitative research methods, including non-obtrusive observation and in-depth interviews with six participants, the research investigates how the vendors’ economic capacities influence their positioning within the market’s spatial layers. The findings reveal that while spatial organization does not directly determine stratification, it indirectly affects it through the vendors’ pre-established economic situations. Vendors with stronger economic capacities occupy more advantageous positions within the market, offering greater opportunities for upward mobility, whereas those in the outermost layers face challenges influenced by weakened economic statuses, exacerbated by political activities. These insights highlight the nuanced interplay between spatial dynamics and economic stratification, suggesting that further research into the political influences on the market’s spatial and economic structures is warranted.